2023
DOI: 10.1021/acs.inorgchem.2c03503
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Effects in the Co-Doping of ZnO Nanowires with Al and Ga Using Chemical Bath Deposition

Abstract: The simultaneous co-doping of ZnO nanowires grown by chemical bath deposition is of high interest for a large number of engineering devices, but the process conditions required and the resulting physicochemical processes are still largely unknown. Herein, we show that the simultaneous co-doping of ZnO nanowires with Al and Ga following the addition of Al­(NO3)3 and Ga­(NO3)3 in the chemical bath operates in a narrow range of conditions in the high-pH region, where the adsorption processes of respective Al­(OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The adsorption process of ion complexes containing the dopant on the charged surfaces of ZnO NWs during CBD is required for the incorporation of dopants, but its nature and magnitude strongly depend on the pH value and dopant. When using column-IIIA dopants including Al and Ga, electrostatic forces dominate the adsorption process such that the incorporation process operates in the high-pH region, where the nonpolar m -plane sidewalls of ZnO NWs are positively charged. , The co-doping of ZnO NWs with Al and Ga was found to incorporate a higher concentration of Ga dopants as Ga Zn than of Al dopants as Al Zn both of them acting as shallow donors owing to energetic considerations . However, this also showed that competitive physicochemical processes can proceed on the nonpolar m -plane sidewalls of ZnO NWs, favoring the incorporation of a given dopant at the expense of the other dopant.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The adsorption process of ion complexes containing the dopant on the charged surfaces of ZnO NWs during CBD is required for the incorporation of dopants, but its nature and magnitude strongly depend on the pH value and dopant. When using column-IIIA dopants including Al and Ga, electrostatic forces dominate the adsorption process such that the incorporation process operates in the high-pH region, where the nonpolar m -plane sidewalls of ZnO NWs are positively charged. , The co-doping of ZnO NWs with Al and Ga was found to incorporate a higher concentration of Ga dopants as Ga Zn than of Al dopants as Al Zn both of them acting as shallow donors owing to energetic considerations . However, this also showed that competitive physicochemical processes can proceed on the nonpolar m -plane sidewalls of ZnO NWs, favoring the incorporation of a given dopant at the expense of the other dopant.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, it is worth noticing that although Cl(I) species reduce the incorporation of Al dopants, it is not fully hampered as Ga(III) species can do. 50 In addition, the Al/Zn atomic ratios before and after thermal annealing are kept constant such that the amount of Al dopants is not affected.…”
Section: Influence Of Doping With Al and CL On The Morphology Of Zno ...mentioning
confidence: 99%
See 3 more Smart Citations